
展开全部
根据二项式定理:
(x+1)^n=1+C(n,1)x+C(n,2)x^2+……+C(n,r)x^r+……+C(n,n)x^n
则所求式子:
右边
=(-1)^n
=(-2+1)^n
=1+C(n,1)(-2)+C(n,2)(-2)^2+……+C(n,r)(-2)^r+……+C(n,n)(-2)^n
=1-2C(n,1)+4C(n,2)+……+C(n,r)(-2)^r+……+C(n,n)(-2)^n
=左边
即:1-2C(n,1)+4C(n,2)+……+C(n,r)(-2)^r+……+C(n,n)(-2)^n=(-1)^n
(x+1)^n=1+C(n,1)x+C(n,2)x^2+……+C(n,r)x^r+……+C(n,n)x^n
则所求式子:
右边
=(-1)^n
=(-2+1)^n
=1+C(n,1)(-2)+C(n,2)(-2)^2+……+C(n,r)(-2)^r+……+C(n,n)(-2)^n
=1-2C(n,1)+4C(n,2)+……+C(n,r)(-2)^r+……+C(n,n)(-2)^n
=左边
即:1-2C(n,1)+4C(n,2)+……+C(n,r)(-2)^r+……+C(n,n)(-2)^n=(-1)^n
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询